2021
DOI: 10.7883/yoken.jjid.2020.947
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Diphtheria and Tetanus Toxoids and Acellular Pertussis (DTaP) Vaccine in Adults in Japan

Abstract: Tetanus toxoid, reduced diphtheria toxoid, and acellular pertussis (Tdap) vaccine is generally used for booster vaccination of infants in Europe and the United States to avoid increased reactogenicity after diphtheria and tetanus toxoids and acellular pertussis (DTaP) vaccination. However, Japan has extended the use of additional DTaP vaccination without reducing the antigen dose for diphtheria and pertussis in adolescents and adults, despite limited reports on its safety in adults. This prospective, observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
2
5
0
Order By: Relevance
“…Similar to our study, previous studies do not show any notable AEs with DTaP-based vaccines in adults [7] , [8] , [9] . In a prospective, observational study evaluating the safety of subcutaneously administered pediatric formulation of DTaP vaccine in Japanese adults, the incidence of local AEs was 51.1%, with the majority of these AEs resolving within 7 days [7] .…”
Section: Discussionsupporting
confidence: 92%
“…Similar to our study, previous studies do not show any notable AEs with DTaP-based vaccines in adults [7] , [8] , [9] . In a prospective, observational study evaluating the safety of subcutaneously administered pediatric formulation of DTaP vaccine in Japanese adults, the incidence of local AEs was 51.1%, with the majority of these AEs resolving within 7 days [7] .…”
Section: Discussionsupporting
confidence: 92%
“…DTaP has a slightly different composition (full‐strength doses of diphtheria, tetanus, and pertussis antigens) than Tdap (full‐strength dose of tetanus antigen and smaller doses of diphtheria and pertussis antigens to maintain immunity), which is approved in the United States and the United Kingdom 23 . Ujiie et al reported that DTaP was well tolerated by Japanese adolescents and adults and could be widely used as a booster in adults as an alternative to the Tdap vaccine 16 …”
Section: Recommendations For Maternal Vaccinationmentioning
confidence: 99%
“…23 Ujiie et al reported that DTaP was well tolerated by Japanese adolescents and adults and could be widely used as a booster in adults as an alternative to the Tdap vaccine. 16 …”
Section: Recommendations For Maternal Vaccinationmentioning
confidence: 99%
See 2 more Smart Citations